Penambahan Tepung Porang (Amorphophallus oncophyllus Blume) pada Bakso Ikan Lele (Clarias gariepinus) - Puteri, Nafisah Eka; Tambulon, Dion; Anggriawin, Mirza; Maryati, Sri; Angraeni, Lia (Universitas Teuku Umar, 2024)
This study aims to explore the effect of adding porang flour on the quality of catfish meatballs, with a focus on texture improvement and its potential use as a natural binder. Porang flour, rich in glucomannan, is used as a substitute for synthetic binders in the meatball industry. The study employs a Completely Randomized Design (CRD) with five treatments (0%, 1%, 2%, 3%, and 4% porang flour) and four replications. The results indicate that the addition of porang flour significantly affects the moisture content, fat content, and organoleptic characteristics of catfish meatballs. A decrease in moisture content was observed with increasing concentrations of porang flour, with the lowest moisture content found in the 4% treatment. The fat content increased with the addition of porang flour but remained within the standard requirements of the Indonesian National Standard (SNI). Hedonic testing revealed that the addition of porang flour improved the panelists' preferences for the color and taste of the meatballs and enhanced the texture at a 3% concentration. However, adding porang flour above 3% resulted in a texture that was too firm. This study recommends using porang flour up to 3% to improve the quality of catfish meatballs, particularly in terms of texture and taste, without compromising the acceptance of aroma.